Vertebral Strength and Estimated Fracture Risk Across the BMI Spectrum in Women. (17th September 2015) - Bachmann, Katherine N; Bruno, Alexander G; Bredella, Miriam A; Schorr, Melanie; Lawson, Elizabeth A; Gill, Corey M; Singhal, Vibha; Meenaghan, Erinne; Gerweck, Anu V; Eddy, Kamryn T; Ebrahimi, Seda; Koman, Stuart L; et al.
ABSTRACT: Somewhat paradoxically, fracture risk, which depends on applied loads and bone strength, is elevated in both anorexia nervosa and obesity at certain skeletal sites. Factor‐of‐risk (Φ), the ratio of applied load to bone strength, is a biomechanically based method to estimate fracture risk; theoretically, higher Φ reflects increased fracture risk. We estimated vertebral strength (linear combination of integral volumetric bone mineral density [Int.vBMD] and cross‐sectional area from quantitative computed tomography [QCT]), vertebral compressive loads, and Φ at L4 in 176 women (65 anorexia nervosa, 45 lean controls, and 66 obese). Using biomechanical models, applied loads were estimated for: 1) standing; 2) arms flexed 90°, holding 5 kg in each hand (holding); 3) 45° trunk flexion, 5 kg in each hand (lifting); 4) 20° trunk right lateral bend, 10 kg in right hand (bending). We also investigated associations of Int.vBMD and vertebral strength with lean mass (from dual‐energy X‐ray absorptiometry [DXA]) and visceral adipose tissue (VAT, from QCT). Women with anorexia nervosa had lower, whereas obese women had similar, Int.vBMD and estimated vertebral strength compared with controls. Vertebral loads were highest in obesity and lowest in anorexia nervosa for standing, holding, and lifting ( p < 0.0001) but were highest in anorexia nervosa for bending ( p < 0.02). Obese women had highest Φ for standing and lifting, whereas women with anorexia nervosa had highest Φ for bending ( p < 0.0001). Obese and anorexia nervosa subjects had higher Φ for holding than controls ( p < 0.03). Int.vBMD and estimated vertebral strength were associated positively with lean mass ( R = 0.28 to 0.45, p ≤ 0.0001) in all groups combined and negatively with VAT ( R = –[0.36 to 0.38], p < 0.003) within the obese group. Therefore, women with anorexia nervosa had higher estimated vertebral fracture risk (Φ) for holding and bending because of inferior vertebral strength. Despite similar vertebral strength as controls, obese women had higher vertebral fracture risk for standing, holding, and lifting because of higher applied loads from higher body weight. Examining the load‐to‐strength ratio helps explain increased fracture risk in both low‐weight and obese women. © 2015 American Society for Bone and Mineral Research.